An empirical investigation into the effects of inorganic corporate expansion on customer-based brand equity: the case of the Renault-Nissan Alliance - Wood, Adam Vance Thomas (2007)
When companies enter into mergers, acquisitions or alliances, their brands become inextricably linked. This paper investigates the effect of mergers, acquisitions and alliances on consumer perception of brands involved. Analysing the Renault-Nissan Alliance of 1999, it uses in-depth, semi-structured interviews to gauge changes to customer-based brand equity post-Alliance. Results show that the level of perceived affiliation between allied brands at consumer level affects the degree of perceived cross-influence between them. The discussion highlights the importance of a successful differentiation strategy to maintaining brand independence and achieving desired synergies. It also illustrates the importance of marketing integration in merger, acquisition and alliance design and implementation.